Genetic approach for species identification: Forensic application of DNA barcoding. (December 2015) - Verzeletti, A.; Cortellini, V.; Cisana, S.; Pretto, S.; Cerri, N.; De Ferrari, F.
Abstract: Species identification is an essential issue in forensic casework. The introduction of DNA barcoding highlighted the expanding use of Cytochrome c Oxidase I mitochondrial gene (COI) as a genetic marker for species identification. This study aims to look at the current method for species identification and how the COI methodology could be applied in a forensic environment. In particular, to test the effective application of COI analysis in forensics, we created experimentally critical conditions such as environmental and mixtures, commonly found in forensic cases, when stain morphology is often compromised.